Double-way interrelations customersâ†”products - Trifu, Alexandru (Information Management and Business Review, 2014)
On the one hand, the impulse in the case of these interrelations and the proper functioning of any company producing/providing services is represented by the needs and motivation of the customers, these aspects leading to determining their behavior in the process of their acceptance / rejection of the products/services they are provided. On the other hand, the products or services should be tailored according to the requirements of the customers and consumers and they should consider the satisfaction of a set of desires and needs, including the ones expressed by the Maslow’s Pyramid of Needs. In order to highlight these multidimensional double-way interrelations, one surely needs, at the same time, to use the marketing sub-function in a case study in symbiosis with the other functions, sub-functions and highlighting tools of the analyzed firm or company. Any purchasing act follows to simultaneous reach more goals, the consumer having to manage between positive motivations and the negative ones, the last category acting as a break. In the double-way interaction, the redirecting of the negative behaviors, along with the improving the supply characteristics are the appropriate ways of winning. A key role in this action is played by the customer loyalty programs which provide a strengthened interrelation and a win-win type beneficial strategy.